2018
DOI: 10.3390/jcm7120548
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Therapy Enhanced Circulating Levels of Endothelial Progenitor Cells and Angiogenesis Biomarkers, Blood Flow, in Ischemic Areas in Patients with Peripheral Arterial Occlusive Disease

Abstract: Background: This study tested the hypothesis that hyperbaric oxygen (HBO) therapy enhanced the circulating levels of endothelial progenitor cells (EPCs), soluble angiogenesis factors, and blood flow in ischemic areas in patients with peripheral arterial occlusive disease (PAOD). Methods: In total, 57 consecutive patients with PAOD undergoing the HBO therapy (3 atmospheres (atm) for 2 h each time) were prospectively enrolled into the present study. Venous blood sampling was performed to assess the circulating l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Hyperbaric oxygen (HBO) therapy is a traditional therapy for patients with ischemic PAOD [ 23 ]. It is proposed that the underlying mechanism of HBO therapy that is predominantly involved in improving ischemic PAOD is the increase of vascular wall permeability and production of hypoxia-inducible factor (HIF)-1α and stromal cell-derived factor (SDF)-1α that enhance the angiogenesis, circulatory EPCs level and blood flow in the ischemic area [ 24 , 25 ]. Unsatisfactorily, the overall limb salvage and progression of the ischemic process have not been significantly decreased in patients receiving HBO therapy [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperbaric oxygen (HBO) therapy is a traditional therapy for patients with ischemic PAOD [ 23 ]. It is proposed that the underlying mechanism of HBO therapy that is predominantly involved in improving ischemic PAOD is the increase of vascular wall permeability and production of hypoxia-inducible factor (HIF)-1α and stromal cell-derived factor (SDF)-1α that enhance the angiogenesis, circulatory EPCs level and blood flow in the ischemic area [ 24 , 25 ]. Unsatisfactorily, the overall limb salvage and progression of the ischemic process have not been significantly decreased in patients receiving HBO therapy [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the diffusion of oxygen into the ischemic organ that creates a hyperbaric environment being extremely limited [ 27 , 28 ] in severe PAOD patients. Interestingly, our recent study demonstrates that HBO increases the number and function of circulatory EPCs [ 25 ]. This finding highlights that HBO may play an accessory role in: (1) promoting the mobilization of EPCs from bone marrow to the circulation; (2) enhancing the capillary/microvascular permeability; (3) augmenting the intrinsic and extrinsic EPCs crossing the vessel wall and homing in on the ischemic area; and (4) acting as a contributor for repairing endothelial functions in the ischemic area via increasing oxygen diffusion into the ischemia, increasing the likelihood of successfully salvaging the limbs of CLI patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms for why MSCs and HBO therapy effectively protect the cells/tissues and organs from any ischemia-related damage always elicit high interest from scientists [35,36]. Currently, abundant data have shown that anti-in ammation, immunomodulation and tissue regeneration as well as cytokine/paracrine effects could be the main mechanisms for MSCs therapy on safeguarding the cells/tissues and organs far away from in ammatory and ischemic related damage [27,28,36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the mentioned cell types, endothelial cells are a favorable source to study migration. Many working groups used either human or bovine endothelial cells in scratch assays and other migration assays [47][48][49][50][51][52][53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%